Biopriming Strategies for Improved Seed Germination in Nutrient Poor Environments: A Comprehensive Review (International Journal of Food and Nutritional Sciences, 2022)
Biopriming is a promising technique that involves treating seeds with beneficial microorganisms, biostimulants, or nutrients to enhance germination, growth, and stress tolerance under various environmental conditions. This comprehensive review evaluates the potential of biopriming strategies to improve seed germination in nutrient-poor environments. We discuss how biopriming enhances germination, including improved water uptake, nutrient assimilation, and resistance to abiotic stress. Additionally, we examine different biopriming agents, such as beneficial bacteria, fungi, and biofertilizers, and their effects on seed germination and plant health. Case studies from various crops and agricultural systems are reviewed to illustrate the benefits and challenges of biopriming. Our analysis highlights the potential for biopriming to promote sustainable agriculture in nutrient-deficient soils and presents future research directions for optimizing this technique.